Spectral and flurescent characteristics of laser dyes for 650-800 nm range - Maslov, V.V. (Functional Materials, 2006)
Spectral, fluorescence and lasing characteristics of several laser dyes for for red and near IR wavelength range have been measured and considered. The laser performances of the dyes have been obtained under monochromatic excitation near maxima of their absorption spectra. The characteristics obtained make it possible to use the dyes purposefully both as active laser media and as fluorescent labels and probes.